China's military presence in the South China Sea and the AUKUS alliance on Indonesia's defense strategy: A review of the land defence aspects - Sukma Wijaya; Joni Widjayanto; Wayan Nuriada (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
As its economy developed, China managed to improve the combat capabilities of its military and defense industry. The presence of China as a new power that has the potential to become hegemony in the region, has caused anxiety for countries in Southeast Asia. Complexity in the region grew after the United States, Britain and Australia formed a new military alliance